Development of Ofloxacin-Loaded CS/PVA Hydrogel for the Treatment of Metritis in Bovine - Priyanka Kumari; Manish Kumar Shukla; Ashutosh Tripathi; Janmejay Pandey; Amit K. Goyal (Drugs and Drug Candidates, 2025)
Background: Metritis, a common postpartum uterine infection in bovines, poses substantial challenges in livestock management, including compromised fertility and economic losses. Poor uterine drug penetration and systemic side effects, necessitating innovative localised delivery systems and limiting current systemic antibiotic treatments. Aim: This study aimed to develop and evaluate the potential effect of the ofloxacin-loaded hydrogel as a localised drug delivery system to treat metritis in bovine. The focus was on achieving sustained drug release, enhanced antibacterial efficacy and reduced inflammation in the endometrium. Materials and Methods: The CS/PVA hydrogel was synthesised using a freeze–thaw method and further optimised for drug encapsulation efficiency (96.7 ± 2.1%), stability and biocompatibility. Physicochemical characterisation included swelling behaviour, mechanical properties and rheological analysis. In vitro drug release profiles in the simulated uterine fluid were assessed over 72 h and antibacterial activity was tested against common uterine pathogens such as Escherichia coli and S. aureus. In vivo studies were conducted on bovines diagnosed with endometritis to evaluate clinical recovery. Results: The SEM image of the ofloxacin-loaded CS/PVA hydrogel resulted in a smooth and porous structure demonstrating larger pore size than the blank. The rheological study suggested higher stability and elastic behaviour. Antibacterial assays on E. coli and S. aureus revealed significant inhibition zones, respectively, indicating potent efficacy. In vivo, evaluated on treated bovine, reduced bacterial loads were exhibited (2.86 × 105A CFU/mL → 6.37 × 102B CFU/mL), clinical improvement was marked and uterine inflammation was resolved. Conclusions: Ofloxacin-loaded hydrogels represent a promising localised treatment for bovine metritis, offering sustained antibacterial action and improved clinical outcomes. This approach addresses the limitations of systemic antibiotic therapies and provides a practical solution for enhanced veterinary care. Further studies are recommended to validate these findings in more extensive field trials and explore commercialisation potential.